Vaginal Microbiota of Spayed Dogs with or without Recurrent Urinary Tract Infections - Hutchins, R.G. (J Vet Intern Med, 2014)
BACKGROUND: Limited information is available regarding the vaginal microbiota of normal spayed dogs and spayed dogs with recurrent UTIs. Vaginal lactic acid‐producing bacteria (LAB) have been associated with decreased frequency of recurrent urinary tract infection in women and may have a protective role within the urinary tract of female dogs. HYPOTHESIS/OBJECTIVES: Spayed dogs with historical recurrent UTI will have decreased prevalence of LAB and increased prevalence of uropathogenic bacterial populations in the vaginal microbiota when compared with the vaginal microbiota of healthy, spayed dogs. ANIMALS: Twenty‐one client‐owned adult spayed female dogs with historical recurrent UTI and 23 healthy, spayed female dogs without a history of recurrent UTI. METHODS: Dogs were placed into a recurrent UTI group or control group in this prospective study. Bacterial populations were isolated and characterized from vaginal swabs obtained from each dog. RESULTS: The most common bacterial isolates obtained from the vaginal tract of all dogs were Escherichia coli (11/44) and S. pseudintermedius (13/44). E. coli was isolated from the vaginal tract of 8 of 21 (38%) dogs in the rUTI group and 3 of 23 (13%) dogs in the control group (P = .08). LAB were isolated from 7 of the 44 dogs. Two of these 7 dogs were in the rUTI group and 5 of the 7 dogs were in the control group. CONCLUSIONS AND CLINICAL IMPORTANCE: The vaginal microbiota of spayed female dogs with recurrent UTI was similar to the control population of normal, spayed female dogs.